Digital Measuring Recovery of Lost Measurements Data - Vladimir Leonovich Yevseyev; Vitaly Grigorievich Ivanenko (Безопасность информационных технологий, 2015)
The article proposes the algorithm for recovery of lost measurements values based on the use of out of the discrete Hartley transform, which is reduced to scalar multiplication coefficient vector by a vector composed of known values.